Enhancing the Conversion Efficiency of Dye-Sensitized Solar Cells based on Betalain Natural Dye as The Potential Photosensitizer: A Review - Sagita, Christyowati Primi (Ma Chung Research Center for Photosynthetic Pigments, 2021)
Natural dyes have gained much attentions as the cheap photosensitizer for dye-sensitized solar cells because of their abundant availability in nature. One of potential natural dyes is betalain dye. Betalain dye mostly can be found in family plant of Caryophyllales. This dye has carboxyl groups and can absorb light until wavelength of 600 nm since betalain dye can be in red-purple color. However, betalain dye is still reported to give a lower efficiency in dye-sensitized solar cells device because of its nature properties as compared to the synthetic dyes. This encourages many researchers to investigate the method for developing betalain ability in purpose to enhance the cell device efficiency. To date, there are two methods having been reported for their positive results in increasing the efficiency of cell device based on betalain dye, i.e., combining the betalain dye with other natural dyes, and selecting the suitable solvent and pH in betalain dye extraction. Therefore, in this review, the summary about potential of betalain dye as photosensitizer and what properties of this dye have as the photosensitizer would be described. The summary of methods for optimizing betalain dye in improving the conversion efficiency of dye-sensitized solar cell also will be presented for better understanding the potential of this dye.